Bond strength and marginal microleakage in restorations photopolymerized with LED and halogen light associated with three application modes of a universal adhesive system: in vitro study - Felipe de Brum RICARDI; Mauro Carlos Agner BUSATO; Priscilla do Monte Ribeiro BUSATO; Márcio José MENDONÇA; Saulo Vinicius da ROSA; Paulo Guilherme Bittencourt MARCHI (Faculdade São Leopoldo Mandic, 2019)
Objective: This study aimed to assess the bond strength and marginal microleakage in composite resin restorations, using the Single Bond Universal adhesive system associated with Ultralux (halogen) and Bluephase (LED) light curing units. Methods: For bond strength, 80 healthy human third molars were divided into halogen light (n=40) and LED (n=40), and subdivided according to the following application techniques for the adhesive system: etch-and-rinse (enamel), self-etching (enamel), etch-and-rinse (dentin), and self-etching (dentin). The teeth were subjected to the microtensile test and the fracture pattern was observed under an optical microscope at 40X magnification; they were analyzed by ANOVA, and Fisher and Tukey's tests (5%). For the marginal microleakage test, 120 class II cavities were prepared in 60 healthy human third molars that were randomly divided into halogen light (n=30) and LED (n=30), and subdivided according to the following application techniques for the adhesive system: etch-and-rinse, selective etching, and self-etching. The teeth were thermocycled 2000 times (±5/55°C), stained in 5% basic fuchsin and sectioned for qualitative and quantitative assessments; they were analyzed by Kruskall-Wallis and Dunn tests (5%). Results: For the bond strength of enamel and dentin, the adhesive application with prior acid etching was better than self-etching (p<0.0001), regardless of the type of light curing unit (p<0.05). Etch-and-rinse showed the lowest microleakage values (p<0.0001). Conclusion: Etch-and-rinse obtained the best results relative to the other application techniques for the adhesive system in both tests, regardless of the type of light curing unit.